A Concise Enantioselective Total Synthesis of (−)‐Deoxoapodine. (15th October 2020) - Yoshida, Kei; Okada, Kosuke; Ueda, Hirofumi; Tokuyama, Hidetoshi
Abstract: We have established a highly convergent 10‐step route for the total synthesis of (−)‐deoxoapodine, which is a hexacyclic aspidosperma alkaloid. The quaternary C5 center of the characteristic tetrahydrofuran ring was constructed by a chiral‐phosphoric‐acid‐catalyzed enantioselective bromocycloetherification in a 5‐ endo fashion and subsequent allylation by using the Keck protocol. Construction of the aspidosperma skeleton features the formation of a nine‐membered lactam by a catalytic C−H palladation/alkylation cascade at the indole 2‐position and an iron‐catalyzed oxidative transannular reaction at a late‐stage of the synthesis. Abstract : In a highly convergent route to (−)‐deoxoapodine, the quaternary center of the tetrahydrofuran ring was formed by an enantioselective organocatalytic bromocycloetherification reaction and subsequent Keck allylation. The aspidosperma skeleton was constructed by a C−H palladation/alkylation cascade at the indole 2‐position to form a nine‐membered lactam and an iron‐catalyzed oxidative transannular reaction at a late stage of the synthesis (see scheme).